Effects of a capacitive-resistive electric transfer therapy on physiological and biomechanical parameters in recreational runners: A randomized controlled crossover trial. (July 2018) - Duñabeitia, Iratxe; Arrieta, Haritz; Torres-Unda, Jon; Gil, Javier; Santos-Concejero, Jordan; Gil, Susana M.; Irazusta, Jon; Bidaurrazaga-Letona, Iraia
Abstract: Objectives: This study compared the effects of a capacitive-resistive electric transfer therapy (Tecar) and passive rest on physiological and biomechanical parameters in recreational runners when performed shortly after an exhausting training session. Design: Randomized controlled crossover trial. Setting: University biomechanical research laboratory. Participants: Fourteen trained male runners Main outcome measures: Physiological (running economy, oxygen uptake, respiratory exchange ratio, ventilation, heart rate, blood lactate concentration) and biomechanical (step length; stride angle, height, frequency, and contact time; swing time; contact phase; support phase; push-off phase) parameters were measured during two incremental treadmill running tests performed two days apart after an exhaustive training session. Results: When running at 14 km/h and 16 km/h, the Tecar treatment group presented greater increases in stride length ( p  < 0.001), angle ( p  < 0.05) and height ( p  < 0.001) between the first and second tests than the control group and, accordingly, greater decreases in stride frequency ( p  < 0.05). Physiological parameters were similar between groups. Conclusions: The present study suggests that a Tecar therapy intervention enhances biomechanical parameters in recreational runners after an exhaustive training session more than passive rest, generating a more efficient running pattern without affecting selected physiological parameters. Highlights: Capacitive-resistive electric transfer therapy was tested in recovery intervention. Capacitive-resistive electric transfer therapy improved strike pattern. No significant physiological differences were detected following the therapy.